Using eosinophil response to predict cardiovascular outcomes in patients with ST- elevation myocardial infarction who undergo primary percutaneous coronary intervention - Joyce Lim; Trent Williams; Lucy Murtha; Nishani Mabotuwana; Conagh Kelly; Doan Ngo; Andrew Boyle (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Objective: Eosinophils have been implicated in mediating the inflammatory response after ST-elevation myocardial infarction (STEMI), but its role as a biomarker predicting major adverse cardiovascular events (MACE) remains unclear. We aimed to evaluate the predictive value of eosinophil response on 30-day and 1-year MACE post primary percutaneous coronary intervention (PCI) after STEMI. Methods: Single centre retrospective cohort study of STEMI patients undergoing PCI. Eosinophil response was defined as the change in peripherally circulating eosinophils cell count at admission minus 48 h post primary PCI. Primary endpoints were 30-day and 1-year MACE. Receiver operating characteristic (ROC) curves were created to identify optimal cut-off predicting MACE. Multivariate logistic regression analyses were used to determine if the ROC cut-off was an independent predictor of MACE. Results: Of the 366 patients in this study (median age 61 years [53.0–71.0]; 267 males [73 %]), 41 patients (11.2 %) and 78 patients (21.3 %) developed MACE at 30-days and 1-year. The optimal ROC curve cut-off predicting MACE was an eosinophil response of greater than −0.05 × 10^9/L (ΔEos > −0.05). It had a sensitivity, specificity, and positive and negative predictive value of 83, 39, 6 and 98 % for 30-day MACE, and 74, 39, 19 and 88 % for 1-year MACE. An ΔEos > −0.05 change was associated with a threefold higher likelihood of MACE at 30-days (OR 3.1, 95 % CI 1.04–9.07, p=0.042), but not 1-year Conclusion: An eosinophil response of −0.05 × 10^9L at 48 h following primary PCI post STEMI is highly sensitive at predicting 30-day MACE, and in its absence, holds a high negative predictive value.